Parapharyngeal space tumors: considerations in 26 cases - Tincani, Alfio José; Martins, Antonio Santos; Altemani, Albina; Scanavini Jr., Rui Carlos; Barreto, Gilson; Lage, Henriette de Toledo; Valério, João Batista; Molina, Giulianno (São Paulo Medical Journal, 1999)
CONTEXT: Parapharyngeal space tumors comprise less than 0.5% of all head and neck neoplasms.1 The majority of these tumors are benign, but surgery is usually required to establish the diagnosis and treat the patients. We present 26 patients treated surgically for tumors arising in the parapharyngeal space (PPS) at the State University of Campinas Hospital – UNICAMP. CASES SERIE: Of these, 17 (65.5%) had benign and 9 (34.6%) malignant neoplasms. The surgical and pathological data relevant to these cases are highlighted, observing any local recurrence, surgical complications and the five-year survival. Neurogenic tumors and soft tissue sarcomas were, respectively, the most frequent benign (35.3%) and malignant neoplasms (44.5%). Benign tumors accounted for the majority of the cases and involved minimal surgical morbidity with no recurrence during a median follow-up of five years. Malignant tumors had a high rate of recurrence and mortality. Surgery is the treatment of choice for PPS tumors. A knowledge of the anatomy of this site is essential for the safe performance of surgical procedures. Malignant neoplasms have a poor prognosis. Fine needle aspiration was helpful in diagnosis of all tumors.